Analysis of the Effectiveness of Periodontitis Treatment Using Antimicrobial Agents - Korniichuk, Oleksandr; Humeniuk, Vasyl; Isakova, Olha; Shchepanskyi, Borys; Antoniv, Vasyl (International Journal of Statistics in Medical Research, 2023)
A combination of systemic antibiotics with scaling may provide an additional advantage over scaling alone in the periodontitis treatment in terms of clinical loss of attachment and change in pocket depth. The use of antibiotics should be justified by a determined need and should not replace adequate local treatment. Different treatment protocols have been proposed, but their indications and efficacy remain controversial. The study aims to analyse the literature on the use of antimicrobial agents for non-surgical periodontal therapy and to compare different protocols for prescribing antimicrobial agents. A search in MEDLINE and EBSCOhost electronic databases was conducted using relevant MeSH words. Targeted studies had to be published within the last five years. Studies were selected based on inclusion and exclusion criteria. Data from selected studies were extracted and analysed. Ten randomized clinical trials were included in the review. The general conclusions of this review indicate a positive effect of antibiotics as an adjunct to non-surgical treatment of chronic periodontitis, regardless of antimicrobial drugs used in the reviewed studies. A prospect for further research is a comparative analysis of the effectiveness of the use of antimicrobial agents and probiotics as an adjunct to the non-surgical treatment of chronic periodontitis.